Nghiªn cøu lý thuyÕt hãa häc lîng tö liªn kÕt hi®r« chuyÓn dêi xanh cña phøc gi÷a CHF3 víi SO2, CO2, CO trong pha khÝ - Trung, Nguyen Tien (Vietnam Journal of Chemistry, 2014)
All calculations were performed at the different high level of theory by using both the two methods MP2, B3LYP and the basis sets 6-31+G(d,p), 6-31++G(2d,2p). The interaction energies are corrected with ZPE and BSSE, about -0.16 and -1.40 kcal.mol-1. The blue-shifts have obtained in all the examined complexes. The electric field of the H-acceptor is the fundamental condition for the blue-shifting hydrogen bond. The C-H bond length upon complex formation is controlled by a balance of two main factors acting in opposite directions. This is rehybridization of C atom and strongly hyperconjugative interaction in complex. The NBO analysis indicates that the H-index is not major reason for physical origin of improper blue-shifting hydrogen bond but the EDT is also reason for the contraction. The RE energy index is also a discriminative factor for the blue-shift and the red-shift in the stretching frequency.